PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN EMERALD FISH STORE DI BANYUANYAR SURAKARTA - anis - sulistyowati (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
The aim of this research is to empirically test the effect of service quality on customer satisfaction at the Emerald Fish Store in Banyuanyar, Surakarta. This type of research uses quantitative methods. The determination of the number of samples was taken according to (J.R. Frankel) 2012 which suggested a minimum sample size of 50 respondents for quantitative research. The sampling technique in this study used purposive and convenience sampling. The data analysis technique in this study used multiple linear regression analysis with the IBM SPSS 24 program. The results of the study showed that the significance of the t-value of the reliability variable was 0.022, the responsiveness variable was 0.033, the assurance variable was 0.017, the empathy variable was 0.002, the physical evidence variable was 0.000 and the variables of reliability, responsiveness, assurance, empathy, and physical evidence of the significance of the F value on customer satisfaction are 0.000. From these results it can be concluded that all independent variables have a simultaneous effect on consumer satisfaction